The effectiveness of a multimodal concept of audition training for music students in coping with music performance anxiety: $hClaudia Spahn, Julia-Caroline Walther and Manfred Nusseck - Spahn, Claudia; Walther, Julia-Caroline; Nusseck, Manfred (Psychology of music, 2016)
Music performance anxiety (MPA) occurs regularly before and during a musical stage performance. Coping with MPA optimizes the performance outcome and plays an i...
First published August 10, 2015
Gesehen am 12.05.2020